+0  
 
0
524
1
avatar+7002 

Solve:

\(y'' - \omega^2y = 0, y(0)=1,y'(0)=1\\\text{Assuming }\omega \neq 0 \)

MaxWong  Jul 25, 2017
 #1
avatar+26814 
+4

Like so:

 

\(y=Ae^{\omega x}+Be^{-\omega x}\\ y'=\omega Ae^{\omega x}-\omega Be^{-\omega x}\\ y''= \omega^2y\)

 

Now use your initial conditions to find A and B.

Alan  Jul 25, 2017

7 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.